2003
DOI: 10.1038/sj.gt.3302115
|View full text |Cite
|
Sign up to set email alerts
|

The cationic region from HIV tat enhances the cell-surface expression of epitope/MHC class I complexes

Abstract: The potential of genetic immunization has been acknowledged for almost a decade, but disappointing immunogenicity in humans has delayed its introduction into the clinical arena. To try to increase the potency of genetic immunization, we and others have evaluated 'translocatory' proteins, which are thought to exit living cells by an uncharacterized pathway, and enter neighboring cells in an energy-independent manner. Several laboratories, including our own, have begun to question these remarkable properties. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…This increases the up-regulation of MHC class I and costimulatory molecules CD80, CD86, and LFA on the surface. Tat contains a cationic domain which may play a role in up-regulation of epitope-MHC class I complexes on the cell surface (50). However, in the present study, the down-regulation of the immune response toward coimmunized Ag is due to up-regulation of IL-10 (immunosuppressive cytokine) and down-regulation of IFN-␥, leading to an overall suppression of the cellular immune response.…”
Section: Discussioncontrasting
confidence: 48%
“…This increases the up-regulation of MHC class I and costimulatory molecules CD80, CD86, and LFA on the surface. Tat contains a cationic domain which may play a role in up-regulation of epitope-MHC class I complexes on the cell surface (50). However, in the present study, the down-regulation of the immune response toward coimmunized Ag is due to up-regulation of IL-10 (immunosuppressive cytokine) and down-regulation of IFN-␥, leading to an overall suppression of the cellular immune response.…”
Section: Discussioncontrasting
confidence: 48%
“…Tat is known to affect all these signalling pathways. Indeed, Tat modulates antigen processing and improves the expression of certain epitope/MHC-I complexes on the surface of APCs leading to an increased stimulation of epitope-specific CD8 + T cells (Signal 1) [15,16,20,29,56]. Moreover, it has been demonstrated that Tat activates NF-κB [19,57,58], a transcription factor critical for the stimulation of T lymphocytes [59].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Tat increases the capability of MDDCs to present both allogeneic and recall antigens, hence potentiating T cell responses against heterologous antigens [95,96]. In addition to the RGD domain, Tat contains in its sequence a short and highly basic region (aa 47-59) termed "protein transduction domain" (PTD), a feature shared with very few other proteins called "penetratins" [201,202], which enables Tat-or PTDconjugated proteins to efficiently enter the cells in an energy-and receptor-independent fashion [203,204]. Thereby, the PTD peptide or the Tat protein have been largely used to deliver conjugated antigens to the MHC class I restricted-antigen presentation pathway, and to increase CTL responses to the conjugated antigen [187,[205][206][207][208][209][210].…”
Section: Immunomodulatory Activity Of Hiv-1 Tatmentioning
confidence: 97%
“…Thereby, the PTD peptide or the Tat protein have been largely used to deliver conjugated antigens to the MHC class I restricted-antigen presentation pathway, and to increase CTL responses to the conjugated antigen [187,[205][206][207][208][209][210]. It has also been suggested that the PTD domain itself, in addition to its antigen-delivery capability, exerts an adjuvant effect on the conjugated antigen, in a fashion similar to poly-L-arginine peptides [211], leading to increased expression of specific MHC-I/peptide complexes and activation of T cell responses [202]. In this context, it was demonstrated that a biologically active Tat protein (86 aa), intracellularly expressed or given extracellularly, modifies the catalytic subunit composition of the immunoproteasome in B and T cell cultures [98,212].…”
Section: Immunomodulatory Activity Of Hiv-1 Tatmentioning
confidence: 99%